Estimation of Subordination Results for a Class of Analytic Functions Defined by Convolution - E. A. Adwan (Recent Advances in Mathematical Research and Computer Science Vol. 8, 2022)
Aims / Objectives: In this chapter, making use the Hadamard product, we present drive several interesting subordination results for a new class of analytic function. Besides, we mention some known and new results, which follow as special cases of our findings.